Performance of Clonal Eucalyptus in Different Agroclimatic Zones of Punjab, India - Luna, R. K.; Thakur, N. S.; Kumar, Vijay (Indian Forester, 2009)
Three experiments were laid at Forest Divisions, Ludhiana (Baddowal, site-I), Gurdaspur (site-II) and Tarn-Taran (site-III) to estimate the productivity of Bhadrachalam Eucalyptus clones. The data was also collected from different private farms. At Ludhiana, clone 413 gave the maximum MAI (mean annual increment) of 28.80 m3/ha/year, over bark and 23.49 m3/ha/year, under bark, at an age of 3 years. The clone 526 performed better at Gurdaspur with maximum MAI (productivity) of 21.15 m3/ha/year, over bark and 17.25 m3/ha/year, under bark. Whereas, at Amritsar, clone 413 was most productive with MAI of 36.07 m3/ha/year, over bark and 29.42, m3/ha/year, under bark, at the age of 2.5 years. The present study revealed that the clone 413 gave outstanding productivity over bark ranging from 28.80 m3 to 36.07 m3/ha/year. However clones like 526, 2045, 2070, and 285 also performed well. The analysis of data from private farms revealed that clone 288 gave MAI of 48.79 m3/ha/year over bark, followed by clone 316 with MAI to the tune of 33.70 m3/ha/year (Private farm at Hoshiarpur) at the age of 4 and 5 years, respectively. Though other clones under study had less productivity nevertheless their productivity was significantly higher than seed route plants. The clonal Eucalyptus gave 2 to 6 times more volume per hectare as compared to the seed origin plants. However, the growth and productivity of clones 407 (Site-III) and 72 (Site-II and III) was at par to the seed route plants, hence should not be recommended for plantations.